Desain Eksperimen Untuk Pengendalian Kadar Air Jamu Simplisia - Nindhira, Arinda Lisna, Ida Nursanti, ST., M.Eng.Sc (2016)
This study discusses the problem of the water content of herbs that are not in accordance with the quality standards set by Department of Health of Indonesia. Quality is one of the most basic factors in a production process that should be considered by the company. Some of the basic characteristics of the production of herbal medicine are taste, smoothness and moisture content to determine the quality of herbal medicine produced. The water content is a critical factor in herbs production, maximum water content in the powder of herbs / simplisia is not more than 10% in order to prevent mold growth. The aim of this study was to identify factors that affect the water content of the milling process in herbal powders, plan making of experimental design in accordance with the level and the influenced factors and also determine a combination of levels of factors that can result in water levels to a minimum, in accordance with the herbal quality standards to achieve maximum quality. Efforts to improve the quality of this research was using Taguchi Method by using a calculation of S/N Ratio and analyzed by ANOVA, processed by using the Minitab 16 software. Experiments using the Taguchi method is said to be more effective and save time compared with experiment manually. The results of the research is to produce the optimum combination to achieve the appropriate water content standard milled herbs that weight 600 kg, the initial moisture content of 10-11% and a 15-hour grind. Based on the calculation of the most influential factor is the time rollers, heavy rollers and initial moisture content. ANOVA analysis explains that there are factor which effect on water content and then Tukey's test explains that all combination have effect same with water content.